Personal Branding of Gus Muhaimin Iskandar Through Social Media - Rahma Munto Via Ningrum; Muhammad Arash; La Mani (Lembaga Bale Literasi, 2026)
The rapid development of social media has made political communication increasingly strategic in enabling political figures to build their personal branding through direct, interactive, and sustained engagement in the digital sphere. This study aims to analyze public perceptions of Gus Muhaimin’s political communication through social media in shaping his political image. The research employed a descriptive-exploratory qualitative approach within a constructivist paradigm using a case study method. Data were collected through non-participant observation of Gus Muhaimin’s social media content on Instagram, TikTok, X, and YouTube, semi-structured interviews with informants selected using purposive and snowball sampling techniques, and digital documentation. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, complemented by thematic analysis. The findings indicate that public perceptions of Gus Muhaimin’s political communication reflect a consistent communication strategy implemented across multiple social media platforms through the integration of visual, verbal, and personal narrative elements, resulting in a coherent political image. The most prominent communication elements contributing to his personal branding include his religious-pesantren identity, the high visibility of his digital content, and an empathetic image toward ordinary citizens. Furthermore, visual narratives and storytelling play a central role in shaping public perceptions by portraying him as a religious, people-oriented, humanistic political figure who is closely connected with younger generations. The study also reveals that this communication strategy has considerable potential to strengthen emotional engagement with digital audiences. However, it continues to face challenges related to maintaining authenticity, ensuring consistency in the substance of political messages, and addressing public sensitivity toward excessive political image-building.